Abolition of zolpidem sensitivity in mice with a point mutation in the GABAA receptor gamma2 subunit. - Cope, D; Wulff, P; Oberto, A; Aller, M; Capogna, M; Ferraguti, F; Halbsguth, C; Hoeger, H; Jolin, H; Jones, A; McKenzie, A; Ogris, W; et al. (2004)
Agonists of the allosteric benzodiazepine site of GABAA receptors bind at the interface of the alpha and gamma subunits. Here, we tested the in vivo contribution of the gamma2 subunit to the actions of zolpidem, an alpha1 subunit selective benzodiazepine agonist, by generating mice with a phenylalanine (F) to isoleucine (I) substitution at position 77 in the gamma2 subunit. The gamma2F77I mutation has no major effect on the expression of GABAA receptor subunits in the cerebellum. The potency of zolpidem, but not that of flurazepam, for the inhibition of [3H]flunitrazepam binding to cerebellar membranes is greatly reduced in gamma2I77/I77 mice. Zolpidem (1 microM) increased both the amplitude and decay of miniature inhibitory postsynaptic currents (mIPSCs) in Purkinje cells of control C57BL/6 (34% and 92%, respectively) and gamma2F77/F77 (20% and 84%) mice, but not in those of gamma2F77I mice. Zolpidem tartrate had no effect on exploratory activity (staircase test) or motor performance (rotarod test) in gamma2I77/I77 mice at doses up to 30 mg/kg (i.p.) that strongly sedated or impaired the control mice. Flurazepam was equally effective in enhancing mIPSCs and disrupting performance in the rotarod test in control and gamma2I77/I77 mice. These results show that the effect of zolpidem, but not flurazepam, is selectively eliminated in the brain by the gamma2F77I point mutation.